Development and investigation of 2.39 μm-lasers for ecological monitoring - Bondarchuk, Ya.M.; Dovgy, Ya.O. (Functional Materials, 2004)
A new approach to development of He-Ne lasers on cascade transitions with radiation wavelength 2.39 μm is considered. Mirrors of the resonator play the part of selective elements. The optimum parameters of laser generation on this transition are analyzed. Рассматривается новый подход к разработке гелий-неоновых лазеров на каскадных переходах с длиной волны излучения 2,39 мкм. Роль селективных элементов играют зеркала резонатора. Рассматриваются оптимальные параметры генерации лазера. Розглядається новий підхід до розробки гєлій-нєонових лaзерiв на каскадних переходах з довжиною хвилі випромінювання 2,39 мкм. Роль селективних елементів грають дзеркала резонатора. Розглядаються оптимальні параметри генерації лазера.